MINI-ACCESS OSTEOPLASTIC THORACOPLASTY IN THE COMBINATION TREATMENT OF PATIENTS WITH FIBROCAVERNOUS PULMONARY TUBERCULOSIS - D. V. Krasnov; D. A. Skvortsov; V. A. Krasnov; N. G. Grishchenko; M. V. Chernova (Туберкулез и болезни лёгких, 2014)
Mini-access osteoplastic thoracoplasty was performed in 130 patients with disseminated fibrocavernous pulmonary tuberculosis. The use of this technique could achieve sufficiently satisfactory and no higher results than that of conventional methods, namely to stop bacterial excretion and to close decay cavities with a 10.7% reduction in the risk of postoperative complications, and considerably decrease intraoperative blood loss.